Sinkronisasi Pengelolaan Sampah di TPA Cipayung Kota Depok: Evaluasi Ketidaksesuaian antara Kapasitas Infrastruktur dan Volume Timbulan Sampah - Mahmud Masulin; Aura Anastria Putri; Dinda Eka Aprilia; Riska Putri Rosdiana (Aljabar : Jurnal Ilmuan Pendidikan, Matematika dan Kebumian, 2026)
Urban waste management often faces a gap between technical capacity and field realities. This study aims to describe the waste processing infrastructure at the Cipayung Final Processing Site (TPA) in Depok City, identify non-technical constraints that cause discrepancies between site capacity and waste volume, and analyze the roles and perceptions of stakeholders. A qualitative descriptive approach with a case study design was employed. Data were collected through participatory observation, in-depth interviews with TPA managers, and documentation. Data analysis followed the Miles and Huberman model, with source and technique triangulation to ensure data validity. The results show that the site capacity and infrastructure (excavators and bulldozers) are not proportional to the daily incoming waste volume, primarily due to low levels of waste segregation at the source. The main non-technical constraints include lack of community participation and weak continuous education. Stakeholder perceptions vary, yet all agree on the need for more effective synergy and communication. This study recommends strengthening collaborative governance, enhancing education based on local wisdom, and making technical adjustments to infrastructure according to local waste characteristics.